Study of the Relationship between Per Capita Income and the Number of National Tourists in Entertainment Tax Revenue Receipt (Case Study in 5 Cities of DKI Jakarta) - Albab, Farah Nisa Ul; Rahayu, Dewi (Digital Business: Tren Bisnis Masa Depan, 2024)
Objectives: This research aims to determine the effect of per capita income and the number of domestic tourists on entertainment tax revenues. This research is based on the DKI Jakarta Province as one of the highest PAD producers in Indonesia. This research uses secondary data. Data was obtained from the DKI Jakarta Regional Revenue Agency, the Central Statistics Agency, and the DKI Jakarta Provincial Government Integrated Data Portal. The analysis tool used is E-Views. Results/findings: The research results show that per capita income has a positive effect on entertainment tax. Other results show that domestic tourists have no effect on entertainment tax. Theoretical contribution: Research on entertainment taxes is still very limited, so the results of this research can add to the literature related to entertainment taxes. Practical contribution: The results of the research can be input for the DKI Jakarta Regional Revenue Agency to create entertainment tax optimization policies. Limitations: This research uses data before Covid-19, namely 2012-2019, so it is necessary to add variables and research years